The Manganan Tradition on the Night of the Kulon Plumpang Well: Religious Values and Local Wisdom - Nurul Hakim; Ikhda Nilla Rosyida; Syafa Layyina Amalia; Shofiyatun Nasuha (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
The manganan tradition is one of the forms of local wisdom that continues to be preserved by the community of Sumur Kulon, Plumpang. This tradition is carried out on certain nights around a well that is believed to have historical and spiritual significance. The community believes that a wali (Islamic saint) once stayed in the area while spreading Islamic teachings, which makes the place regarded as sacred and blessed. In the past, the well was known for its clear water that could be consumed by the local community, making it a symbol of life and divine blessing for the surrounding society. The manganan tradition is performed through a communal meal preceded by prayers and tahlil as an expression of gratitude to Allah SWT. This activity is not only understood as a cultural ritual but also as a form of respect for religious figures who played a role in spreading Islam in the region. In addition, the tradition reflects various religious and social values, such as gratitude, togetherness, mutual cooperation, and respect for historical heritage. Furthermore, the manganan tradition also plays an important role in strengthening social bonds among community members and preserving the local cultural identity. Thus, this tradition represents a harmonious integration between religious values, historical memory, and local wisdom that continues to be maintained by the community to this day.